Characterization of the use of corticosteroids in the treatment of sepsis or septic shock - Talarico Carreira, Danielle; Farias, Anibal Danilo (Salud Integral y Comunitaria, 2025)
Introduction: sepsis and septic shock are currently a serious public health problem, as it is a disease with a high rate of complications and because it is one of the main causes of admission to the intensive care unit (ICU). In addition, in recent decades the number of patients diagnosed with sepsis is growing every year. Objectives: to determine whether the implementation of corticosteroids in the basic treatment of patients who are in sepsis or suffering from septic shock brings benefits or harms. Method: this systematic review is based on a thorough search in the Medline (Pubmed) and Google Scholar databases, the analysis of the publications was chosen between the years 2010 to 2024. Result: according to the evidence found in the 20 articles reviewed, the use of corticosteroid therapy reduces the time in some patients who are in shock, mainly those who do not respond adequately to conventional vasopressin fluids and drugs. However, it is still under discussion whether these data can be interpreted as beneficial for patients in terms of mortality. And whether the benefits are the same for septic patients given the potential risks that corticosteroids cause to the immune system and the hyperglycemia evidenced in some studies. Conclusion: The results of the systematic review and the cohort studies analyzed suggest that there are still many disagreements on the matter, but most recommend the use of corticosteroid therapy as part of the treatment of patients with septic shock and not in sepsis.